(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2017)
This study concerns the assessment and treatment of problem behaviors of two people diagnosed with depression in which the events motivating antecedents and consequent for problem behaviors consisted of social attention and escape demands. The participants were women who reported receiving this diagnosis since adolescence. To evaluate the reports of problem behaviors, functional assessment strategies were employed, such as indirect observation, direct observation and functional analysis with four especially conditions: attention, escape demand, control and alone. The participants exhibited high rates of problem behaviors during the attention and escape demands condition showing the control of motivating antecedents and of consequent reinforcements. In the control condition, it was possible to observe the effectiveness of density of reinforces, and in the alone condition the behavior-problem did not occur. To treat the reports of problem behaviors the intervention program included a differential reinforcement (DRA), plus extinction (EXT) procedure, using the reverse-replication design followed by follow-up. It was observed that the DRA plus EXT decreased reports of problem behaviors and increased reliable reports of desired behavior.